Relationship of Visceral Adipose Tissue With Dilated Perivascular Spaces - Qi, Yunli; Lin, Mengqi; Yang, Yunjun; Li, Yanxuan (Frontiers in Neuroscience, 2021)
Background: Dilated perivascular spaces (dPVS) are considered to be a type of cerebral small vessel disease (CSVD) as well as an important part of the glymphatic system. Although obesity has been shown to play a significant role in the development of CSVD, there are no studies addressing the correlation between obesity and dPVS. We aimed to study the relationship between abdominal fat distribution and dPVS in neurologically healthy cohorts. Methods: A total of 989 subjects, who were examined during a health examination project, were included in this study. We measured both visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) areas using abdominal computed tomography. The dPVS scores were also evaluated in the basal ganglia (BG) and the centrum semiovale (CSO). Results: In a multivariate ordinal regression analysis, the relationship between VAT area and CSO-dPVS scores remained significant (β [95% confidence interval CI = 0.00003395] [0.00001074–0.00005716], P = 0.004), especially in male cohorts (β [95% CI] = 0.00004325 [0.00001772–0.00006878], P = 0.001) after adjusting for age; sex; and glucose, creatinine, uric acid, high-density lipoprotein, and low-density lipoprotein levels; while no association was found between SAT area and dPVS scores. The effects of quartile VAT area on CSO-dPVS were also significant in male cohorts (odds ratio [95% CI] = 1.33 [1.139 – 1.557], P < 0.001). Conclusions: We demonstrated a positive association between VAT and CSO-dPVS scores in a healthy cohort, which was more prominent in males.